Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/14651858.cd013110
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training for bronchiectasis

Abstract: This is a protocol for a Cochrane Review (Intervention). The objectives are as follows:To determine the effects of exercise training compared to usual care on exercise tolerance, HRQoL, incidence of acute exacerbations and hospitalisation, clinical respiratory and mental health symptoms, and physical function in people with stable or an acute exacerbation of bronchiectasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 50 publications
0
22
0
1
Order By: Relevance
“…The results of this study showed that breathing exercises significantly reduced heart rate and respiratory rate compared to the reference and waiting list group. During meditation, the body enters a state of relaxation response by decreasing heart rate, respiratory rate, blood pressure, and muscle tone and increasing alpha brain waves, which in turn reduces stress (Lee, gordon & Osadnik, 2018;Lee et al, 2016;Lee & Jang, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study showed that breathing exercises significantly reduced heart rate and respiratory rate compared to the reference and waiting list group. During meditation, the body enters a state of relaxation response by decreasing heart rate, respiratory rate, blood pressure, and muscle tone and increasing alpha brain waves, which in turn reduces stress (Lee, gordon & Osadnik, 2018;Lee et al, 2016;Lee & Jang, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This approach is supported by strong evidence that PR delivers meaningful improvements in exercise capacity, symptoms and QoL [3], as well as reductions in hospitalisations [4] and perhaps even improvements in survival [5]. More recently, PR has become the standard of care for patients with other chronic respiratory diseases, including bronchiectasis, pulmonary hypertension, ILD and lung cancer, underpinned by positive findings from clinical trials [6][7][8][9].…”
Section: Guest Editors VIImentioning
confidence: 98%
“…We included clinical trials of pulmonary rehabilitation compared to usual care in patients with stable chronic airways disease, identified from published systematic reviews [1,4,8]. Systematic reviews were identified from Medline (Ovid) searches using keywords for diagnosis (COPD, asthma or bronchiectasis) and rehabilitation or exercise training, limited to "review articles" or "topic reviews (Cochrane)".…”
Section: Types Of Studiesmentioning
confidence: 99%
“…Pulmonary rehabilitation is a highly effective intervention to enhance exercise capacity, improve symptoms and reduce hospitalisations in people with chronic airways disease [1][2][3][4]. Pulmonary rehabilitation is defined as the delivery of "patient tailored therapies … designed to improve the physical and psychological condition of people with chronic respiratory disease and to promote the long-term adherence to health-enhancing behaviours" [5].…”
Section: Introductionmentioning
confidence: 99%